A solution to help learners conduct on-line literature searches for reference books - SUGIYAMA, Hisako (Igaku Toshokan, 2004)
Tokyo Women's Medical University Library holds books which serve as good guides to problem-based learners. During self-study, students often use only OPAC to search for reference books and often fail to accomplish efficient literature search. The problem may be due to the difference between “uncontrolled vocabulary” students use for searching books and “control led vocabulary” librarians use for indexing books. With the current index system, a student cannot usually locate the reference books using subject headings and key words learnt from their teachers. The classification number is usually more useful than the subject headings when searching for books. To solve this problem, several analyses were performed and a literature search system was created. The additional search system is more user-friendly and helps students to locate reference books faster. Also, the new system leads students directly to book stacks where related books on the matched topic are placed.